Expanding Horizons: Analyzing Men-Focused Research in Adult Education Journals 2003-2023 - Lihua Shang; Lisa Baumgartner (Adult Education Research Conference, 2025)
We reviewed men-centered articles in adult education journals and AERC Proceedings from 2003-2023. We uncovered how men were portrayed and how hegemonic masculinity was demonstrated.
Keywords: Men; hegemonic masculinity; literature review; adult education